Awareness of contraception and the reasons for having more than two children: a survey among antenatal women - Sambath, Shanthadevi; Balasubramanian, Thangamani; Ilangovan, Shanthirani; Aravazhi, Mahalakshmi; Shanmuganathan, Shanthavibala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: India accounts for 2.4% of world’s total surface area, yet it supports 17.5 % of the world’s population. 42 % of population increase is contributed by birth beyond two children per family. Even though variety of safe and effective methods of contraception available, many women are not using any method of contraception. Methods: A cross sectional study was conducted in 130 antenatal women with two or more living children attending antenatal OPD in Government Theni medical college Hospital. They were interviewed with predesigned questionnaire after getting informed consent. Results: 96.9% of women were aware /heard about any one method of contraception, whereas only 12.3% of women had ever used contraceptives. The main reason for not using contraception was lack of knowledge about the benefits of contraceptive methods, husband’s opposition and fear of side effects. The most common reasons to conceive after two or more living children were desire to have male baby (58.5%) and unintended pregnancy (23.1%). Conclusions: The study reveals that more efforts are required to motivate couples for contraceptive usage and educate them about gender equality, to encourage girl child education so that avoiding too many pregnancies, thus to achieve reduction in maternal and perinatal mortality and morbidity along with population stabilization.